(untitled) (Research, Society and Development, 2022)
Pomegranate is known for its beneficial effects on health, mainly for its antioxidant properties and is widely cultivated in different regions of the world, which reflects the great diversity of fruit composition. Thus, the objective of this work was to evaluate the physical, physicochemical, biochemical and proximate composition of pomegranate cv. Comum cultivated in the west of São Paulo. The fruits used were harvested at the commercial maturation stage, in the municipality of Alvares Machado, Presidente Prudente region, state of São Paulo and evaluated for weight, firmness, color, pH, soluble solids (SS), titratable acidity (TA), Ratio (SS/AT), total phenolic compounds, antioxidant activity by DPPH, total monomeric anthocyanin, mineral composition, moisture, ash, proteins, lipids, fibers, reducing sugars and total caloric value. Pomegranate fruits cv. Comum skin had an orange color and pulp (sarcotesta) red-violet. Potassium (K) was the predominant macronutrient in the skin and pulp. The pulp had a high content of soluble solids and a low content of titratable acidity, characterizing a sweet taste. The peel showed higher content of total phenolic compounds and antioxidant activity in relation to the pulp. The pulp had the highest total caloric value.